Paneth cells in innate immunity and inflammatory bowel disease - Keshav, Satish (Henry Stewart Talks, 2009)
Position and structure of Paneth cells, Produce diverse protein products, Ultrastructure, Lysozyme, Paneth cell defensins, Salmonella infection, Antimicrobial function, Zinc, IgA, Effects of lineage ablation, TNFalfa, Expression of immune-related genes, Potential role in human disease, Are Paneth cells involved in the pathogenesis of IBD?, Ulcerative colitis and Crohn's disease, The NOD2 gene, Control of Paneth cell secretion, Paneth cells highly responsive to MPD, Defensin expression, Paneth cell morphology and gene expression are altered in IBD